Caracterizações dos aspectos histopatológicos e do inflamassoma NLRP3 na COVID-19 - Gustavo Palmer Irffi (2022)
The COVID-19 is the result of the infection by the SARS-CoV-2, that infects the target cells and activates many inflammatory mechanisms, such as NLRP3 inflammasome, that releases IL-1β, IL-18 and Caspase-1, contributing to a systemic inflammatory response. The study of morphological aspects resulting from fatal COVID-19, through minimally invasive autopsy, represents an important opportunity for a better understanding of this new disease. With the aim of characterizing the histopathological aspects and evaluating the NLRP3 inflammasome in fatal COVID-19, this observational, cross-sectional and unicentric study analyzed 50 cases samples, collected by minimally invasive autopsy, of patients who died of COVID-19 in the Eduardo de Menezes - MG Hospital, during the year of 2020. The samples showed high histological representativeness. The main histopathological lesion observed were diffuse alveolar damage (64,45%) in the lungs and foci of inflammatory infiltrate in the heart (32,61%), liver (70%) and kidney (21,4%). In addition, were observed high percentages of ischemic heart lesions, hepatic steatosis, splenic congestion, and acute tubular injury. The immunohistochemical expression of NLRP3 showed high reactivity in the lungs, heart and kidneys, with statistically significant associations of IL-18 (p-value = 0,004) in the lung and of IL-1β (p-value = 0,002) in the kidney. The results of this study let us to conclude that the minimally invasive autopsy makes available adequate anatomopathological examination of death verification, and that fatal COVID-19 has an important systemic inflammatory component, with participation of the NLRP3 inflammasome.